ANALISIS PENGARUH KOMITMEN PROFESIONAL, INTENSITAS MORAL, DAN LOCUS OF CONTROL TERHADAP INTENSI WHISTLEBLOWING - Fiddini, Fadia Tara; Ridaryanto, Petrus (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2024)
It is not easy for individuals to decide to carry out whistleblowing. Individuals will be faced with the dilemma of whether to blow the whistle or just let the violation happen because of concerns about the negative impact it will have on them. Therefore, it is important to research the factors that can influence whistleblowing intentions, so that organizations can understand the dynamics behind individual decisions to report violations or unethical behavior. This research aims to analyze the influence of professional commitment, moral intensity, and locus of control on whistleblowing intentions. In collecting data, the author distributed questionnaires online with a research sample of 45 respondents who were employees of 3 companies in Jakarta that had implemented a whistleblowing system, namely PT Telkom Indonesia, PT Telekomunikasi Selular, and PT Bursa Efek Indonesia. The collected data was analyzed using multiple regression analysis method. The research results show that professional commitment has a positive influence on whistleblowing intentions. Meanwhile, moral intensity and locus of control have no influence on whistleblowing intentions. Keywords: Professional Commitment, Moral Intensity. Locus of Control, Whistleblowing Intentions